Escitalopram treatment ameliorates chronic immobilization stress-induced depressive behavior and cognitive deficits by modulating BDNF expression in the hippocampus - Shilpa Borehalli Mayegowda, Bhagya Venkanna Rao, Byrathnahalli Suryanarayana Rao Shankaranarayana Rao (Journal of Applied Pharmaceutical Science, 2024)
Major depressive disorder (MDD) affects 21% of the global population. Chronic exposure to stressful situations may affect the onset, progression, and biochemical alterations underlying MDD and associated cognitive impairments. Patients exhibiting MDD are mainly treated with several antidepressants; one is escitalopram, a selective serotonin reuptake inhibitor. However, whether or not it mitigates chronic stress-induced cognitive deficits is unknown. The present study exposed rats to chronic immobilization stress (CIS) 2 hours/day for 10 days. Then, escitalopram (5 mg and 10 mg/kg i.p.) was administered for 14 days and subjected to the elevated plus maze, open field test, forced swim test, sucrose preference test, and radial arm maze task. A different set of animals were used to assess the vascular endothelial growth factor (VEGF), glial fibrillary acidic protein (GFAP), and brain derived neurotrophic factor (BDNF) levels in the hippocampus, frontal cortex, and amygdale. Our data suggest that escitalopram significantly protected CIS-induced spatial learning and memory deficits, behavioral depression, and anxiety. Furthermore, escitalopram (10 mg/kg) shows a remarkable recovery of dentate gyrus and hippocampal atrophy. In addition, the restoration of molecular markers BDNF, VEGF, and GFAP expression is also implicated in the neuroprotective mechanisms of escitalopram. Our results suggested that esciatlorpam restores cognitive impairments in stressed rats by regulating neurotrophic factors and astrocytic markers.
Keywords: Hippocampus, escitalopram, neurotrophic factors, neuronal plasticity, cronic stress